Christianity’s Laymen and Teaching of Mathematics in Lithuanian School - Ažubalis, Algirdas (Acta Paedagogica Vilnensia, 2000)
The period under analysis distinguishes three stages: 1) teaching in parish schools and “bakalorijos” (private village schools) (till 1864); 2) period of secret school (1864-1904); 3) private Lithuanian school after regaining press and during the period of World War I (1904-1918) and school in Independent Lithuania (1918-1940). In the first period are important mathematics teaching works in Lithuanian school of priests J. Stanevičius, M. Ceraskis, M. Brundza, A Juška and V. Juzumas. On the second period can be distinguished priests J. Katek and S. Gimžauskas, in the third period – priests A Dambrauskas-Jakštas and O. T Volk, also christianity’s laymen P. Dovydaitis. A Mažylytė, I. Malinauskas, K. K. Raičinskis, O. E. Stanaitis.